If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -1 = 25 Reorder the terms: -1 + 4y = 25 Solving -1 + 4y = 25 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 4y = 25 + 1 Combine like terms: -1 + 1 = 0 0 + 4y = 25 + 1 4y = 25 + 1 Combine like terms: 25 + 1 = 26 4y = 26 Divide each side by '4'. y = 6.5 Simplifying y = 6.5
| 2x+2=-1x+26 | | ((m^6n)^-2(m^2n^-2)^3)/m^-1n^-2 | | 9x+4=-18 | | 2/4p=3/4p+2 | | 15/17-2/34 | | 40=6x+16 | | R(4)+8= | | 10=6x+16 | | 15x+20x=1800 | | 1.8+32=90 | | -8y+8=37x-7 | | -3(5x+-4)=21 | | (-7p/2)=(-7/8) | | 13x^2+21=-5x^2+22 | | (-7p/2)(-7/8) | | 32x=1 | | (2-7x)+(2x+1)= | | 2-4x=4x+10 | | 5-2n=5 | | 4x+9=34x | | 4x=2x+2+3x-3 | | 0=6(x+2)(x-1) | | x^4-10x^2+34=0 | | 9x+6=27 | | X/2=57 | | 5/3=y/9 | | R(4)= | | 7x+280=8x+278 | | F(3)+3= | | 5(3x+4)=0 | | 34=3x+10 | | 5w+7-2(-7w-4)=3(w-1) |